Cultural Differences in Visual Contents in Picture Books - Kuwabara, Megumi; Alonso, Jannette; Ayala, Darlene (Frontiers in Psychology, 2020)
Previous studies investigating cultural differences in attention and perception have shown that individuals from Western countries (e.g., the U.S.) perceive more analytically whereas individuals from East Asian countries (e.g., Japan) perceive more holistically (e.g., Nisbett & Miyamoto, 2005). These differences have been shown in children as young as three years old (Kuwabara & Smith, 2016). To reflect cultural influences on cognition, specifically on attention and perception, this study investigated potential differences in the visual environment. In this study, we focused on one of such visual environments that young children are exposed to regularly and influence other domains of development, picture books (Horst & Houston-Price, 2015). 37 U.S. picture books and 37 Japanese picture books were coded for visual contents – how visually crowded – by computer software from the National Institute of Health (NIH) and human coders. Results show that the U.S. picture books are more visually crowded than the Japanese books by the software, but contained more objects than the Japanese books as expected, which reflect well with the cultural differences in attention observed in young children in previous studies. However, the results differed based on the target ages of the books. The implication of the current study is discussed as a reflection of the mutual constitution between culture and psyche.